Study of Thin Film Copper Electrodeposition on Carbon Substrate for Thin Film Battery Electrode Application - Sanat, Nurul Huda; Nmaya, Muhammad Muhammad; Isa, Muhammad Jibrin; Kimpa, Mohammed Isah; Agam, Mohd Arif (Journal of Science and Technology, 2016)
The electrodeposition of copper onto carbon substrate was studied in 0.5 M of CuSO4 solution at various applied voltages; 2.0, 4.8 and 6.0 V. The electrodeposition was carried in an electrochemical cell with copper as the anode and carbon as the cathode. The influence of electrodeposition parameters on the thickness of deposits and surface roughness of copper films were studied in detail using Atomic Force Microscopy (AFM). The current value increases with the increasing of applied voltage. Charge-discharge test was performed in 0.5 M and 1.0 M of HCl, and revealed that high concentration of electrolyte resulted high surface roughness and thickness of copper film.Â